2017
DOI: 10.1038/s41598-017-05879-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the occurrence, spatiotemporal variations and geoaccumulation of fifty-two inorganic elements in sewage sludge: A sludge management revisit

Abstract: The limited information about the sludge quality has made its management a top environmental challenge. In the present study, occurrence and the spatiotemporal variations of 52 inorganic elements were investigated in the sludge samples from three wastewater treatment plants (WWTPs) in Xiamen city, China. The results showed, the occurrence of 49 elements with the concentrations in the range of >125–53500 mg kg−1 dry sludge (DS) for commonly used industrial metals, 1.22–14.0 mg kg−1 DS for precious metals, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…However, no attempts were made to quantify these industrial inputs. Elevated concentrations of REEs were also reported from three different WWTPs in China and were assigned to industrial sources ( Suanon et al., 2017 ). In the same study, only the enrichments relative to the average crust were determined and the quantitative industrial inputs of the respective elements were not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…However, no attempts were made to quantify these industrial inputs. Elevated concentrations of REEs were also reported from three different WWTPs in China and were assigned to industrial sources ( Suanon et al., 2017 ). In the same study, only the enrichments relative to the average crust were determined and the quantitative industrial inputs of the respective elements were not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…One sludge however showed higher normalized values for La and Ce (0.45 and 0.6, respectively), which was attributed to elevated concentrations of these elements in the wastewater. Sludge investigated by Suanon et al. (2017) also revealed crust normalized REE ratios smaller than 0.6 in different digested sludges from the US ( Verplanck et al., 2010 ), and PAAS-normalized REE-patterns appeared flat without any pronounced Ce enrichments.…”
Section: Resultsmentioning
confidence: 97%
“…Cerium concentrations of up to 153 mg kg −1 were reported from the UK and were attributed to inputs from the glass industry ( Vivian, 1986 ). More recently, a monitoring study of three WWTP in China ( Suanon et al., 2017 ) and a survey of the metal contents in sewage sludge from Switzerland ( Vriens et al., 2017 ) revealed that sewage sludge can contain up to ≈800 mg kg −1 Ce in the total suspended solids (TSS). The median Ce content of municipal sewage sludge from Switzerland (≈20 mg kg −1 ; n = 64), however, was below its average crustal abundance (60 mg kg −1 ( Voncken, 2016 )).…”
Section: Introductionmentioning
confidence: 99%
“…These metals mainly originate from the aqueous phase of the wastewater, and then concentrate in the sludge during the treatment processes like precipitation, coagulation, adsorption etc. Recently, a studied was conducted in China by [31], and over 50 metallic elements including industrial commonly used PTE, rare earth elements and precious metals; were investigated in sewage sludge from different wastewater treatment plants from different region. Results revealed broad range of concentrations of the elements ranging from >125-53,500 mg kg −1 dry sludge (DS) for commonly used industrial metals, 1.22-14.0 mg kg −1 DS for precious metals, and 1.12-439.0 mg kg −1 DS for rare earth elements.…”
Section: Main Sources Of Metals In the Soilmentioning
confidence: 99%